High-heat-load and low-permeability flexible fiber-based composite fabric and preparation method thereof

By introducing isocyanate bridge agent in the extrusion processing stage of TPU composite material, the modified TPU is in a semi-cured crosslinking state, which solves the shortcomings of fiber-based TPU composite material in terms of heat load resistance and barrier properties, and achieves higher heat Stability and barrier properties.

CN119459067APending Publication Date: 2025-02-18CTA HI TECH TEXTILES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411710312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing fiber-based TPU composites have shortcomings in terms of thermal load resistance and barrier properties, especially in the high temperature environment, the strong decrease in the thermal load of the joints, which affects the airtightness and safety of use.

Method used

By introducing isocyanate bridge agent in the extrusion processing stage of the TPU, the modified TPU is in a semi-cured crosslinked state to form an intercrosslinked structure to improve its thermal stability and barrier properties.

Benefits of technology

It improves the thermal stability and thermal load strength of TPU composite materials, enhances the barrier properties of small molecular substances, improves the airtightness and safety of the joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119459067A_ABST
    Figure CN119459067A_ABST
Patent Text Reader

Abstract

The invention provides a high-heat-load and low-permeability flexible fiber-based composite fabric and a preparation method thereof. The high-heat-load and low-permeability flexible fiber-based composite fabric comprises a first TPU layer, a first bonding layer, a base cloth layer, a second bonding layer and a second TPU layer which are sequentially arranged, the first bonding layer and the second bonding layer comprise one or more of polyurethane resin, a solvent, diisocyanate, polyisocyanate and a polyether siloxane copolymer. The preparation method has the beneficial effects that a full-process high-heat-load and low-permeability composite material production process is provided, the composite material is excellent in performance and can be applied to various special fields such as high-altitude balloons, and the application range of a conventional TPU composite material is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of industrial textiles, and in particular relates to a high heat load, low permeability flexible fiber-based composite fabric and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane (TPU) is a polymer material that has developed rapidly in recent years. TPU can be made into thin films by casting, blowing and calendering. It has the superior characteristics of good elasticity, toughness, wear resistance, good cold resistance, environmental protection and non-toxicity, and has gradually replaced rubber and PVC. TPU composite fabric is a new type of composite material formed by laminating one or more layers of textile materials with TPU film. It has good processability and high efficiency of product molding. The processing process is green and environmentally friendly. Compared with traditional rubber materials, TPU products are softer, lighter, and more efficient to process and shape. The finished products are flexible and versatile during use. However, unlike the vulcanization process of rubber, TPU materials always maintain their thermoplastic properties, which also leads to some functional deficiencies, especially in terms of heat load and barrier properties. Many application scenarios of TPU composite fabrics are mostly for inflation or temporary storage of liquids, such as in moored balls or airship skin composite materials. The current solution is often a composite multi-layer co-extruded film material, by introducing a PA or EVOH layer with high barrier properties, and also introducing PVDC or polyvinyl alcohol as a barrier layer in the coating process. However, the introduction of multiple materials will often lead to low adhesion of the material interface, and the material's feel and flexibility will also deteriorate. It is not conducive to the folding and long-term use of products; there are certain problems in the barrier properties and heat load resistance of TPU composite materials used alone. Compared with traditional barrier materials, due to the low crystallinity of TPU, there is a large gap between molecular weights, and small molecular weight gases such as helium are easy to penetrate, making it difficult to meet the barrier requirements for helium or hydrogen. At the same time, it must withstand high-temperature radiation when floating at high altitudes. The bladder material under pressure has high requirements on the strength of the seam. In addition to the strength of the seam itself, good thermal stability and heat load are also key factors in maintaining the seam from cracking. The current TPU thermoplastic characteristics have no chemical bonds between molecules. Under high temperature conditions, TPU softens, resulting in a decrease in the heat load strength of the seam, affecting the air tightness of the seam. Fiber-based TPU composite materials are also a typical application as soft containers, which can store fuel. However, fuel has a certain degree of wetting and permeability to TPU materials. The current soft oil storage container materials are generally thicker to reduce the oil permeability. The increased film thickness will inevitably lead to an increase in the mass per unit area of ​​the material. While the cost increases, it is not conducive to storage and transportation at the product end, especially in some scenarios where lightweight materials are required, such as drone oil bladders, which require that the material cannot be too heavy. This puts higher requirements on existing materials; when the oil bladder material is used outdoors, it is also faced with a high temperature solar radiation environment, and there is also a problem of strong thermal load reduction at the seam position, which affects the safety of the seam use. The current method of sewing the seams or widening the width of the welding belt generally results in excessive seam thickness and high stiffness, which affects the flexibility of the product.

[0003] As mentioned above, existing fiber-based TPU composite materials have certain deficiencies in heat load resistance and barrier properties. Current solutions generally lead to increased process complexity and cost. The present invention modifies TPU during the extrusion processing stage by introducing an isocyanate bridging agent to modify TPU into a semi-cured cross-linked state. On the one hand, it does not affect its melt welding processing characteristics, and on the other hand, it forms bonds between molecules, reduces the molecular distance, and improves its barrier properties to small molecules. The cross-linked structure formed by the chemical reaction of the alkyd groups in the polyurethane effectively improves its thermal stability and heat load strength. Summary of the invention

[0004] In view of this, the present invention aims to provide a high heat load, low permeability flexible fiber-based composite fabric and a preparation method to solve at least one technical problem in the background technology.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: A high heat load, low permeability flexible fiber-based composite fabric comprises a first TPU layer, a first adhesive layer, a base fabric layer, a second adhesive layer and a second TPU layer which are arranged in sequence.

[0006] Furthermore, the first adhesive layer and the second adhesive layer include one or more of polyurethane resin, solvent, diisocyanate, polyisocyanate, and polyether siloxane copolymer.

[0007] Furthermore, the first adhesive layer and the second adhesive layer each include, by mass fraction: 100 parts of polyurethane resin, 20-30 parts of solvent, 2-3 parts of isocyanate, 8-10 parts of polyisocyanate, and 1-5 parts of polyether siloxane copolymer.

[0008] Furthermore, the first TPU layer and the second TPU layer include thermoplastic polyurethane elastomer, polyisocyanate powder with PE as carrier, and white oil.

[0009] Furthermore, the first TPU layer and the second TPU layer include, by mass fraction, 100 parts of thermoplastic polyurethane elastomer, 1-10 parts of polyisocyanate powder with PE as a carrier, and 2-4 parts of white oil.

[0010] Furthermore, the base fabric layer is one of high-strength nylon or high-strength polyester.

[0011] A method for preparing a high heat load, low permeability flexible fiber-based composite fabric comprises the following steps: S1: hot rolling treatment of both sides of the base fabric; S2: mixing the materials of the adhesive layer to obtain a coating of the adhesive layer, and coating both sides of the base fabric with a scraper to obtain a coated base fabric; S3: The PE powder containing polyisocyanate, white oil and TPU particles crushed by low temperature granulation enter the screw in proportion, and the mixed melt is preheated to form a semi-cured cross-linked elastomer, which is then hot-pressed and laminated to the two sides of the coated base fabric obtained in step S2, and cooled and shaped in steps to obtain a flexible fiber-based composite fabric.

[0012] This application uses high-strength base fabric hot pressing to maintain the flatness of the material, and different auxiliary agent ratios of the adhesive to improve the interface adhesion between the glue and the base fabric and enhance the film-forming effect. Diisocyanate and polyisocyanate are compounded to increase the crosslinking degree of polyurethane and enhance the weather resistance of the material.

[0013] Furthermore, the hot rolling temperature in step S1 is 160-180° C., and the hot rolling pressure is 80-100T.

[0014] Further, in step S2, coating both sides of the base fabric to obtain the coated base fabric comprises: coating one side of the base fabric first, drying at a temperature of 140-160°C, and applying a sizing amount of 20-40 g / m 2 , drying time 3-6 minutes, repeat the above operation and coat the other side.

[0015] Step S3 includes mixing the PE powder containing polyisocyanate, white oil and TPU particles which have been granulated and crushed at low temperature in a dew point dry state of -40 degrees Celsius, and automatically mixing them into the screw through a metering scale, the temperature of the screw extrusion section is strictly controlled at 140-150°C, so that the TPU and the polyisocyanate are mixed but no cross-linking reaction occurs, the temperature of the connection section is set to 160±5 degrees Celsius, the mixed melt is heated and preheated, the die head temperature is set to 180-200°C, the isocyanate -NCO and the polyol hydroxyl (-OH) are condensed to form a semi-cured cross-linked elastomer, the extrusion speed is controlled at 8-10rmp, the melt melting mixing and cross-linking bridging time is strictly controlled to prevent the reaction from being too sufficient and accumulating on the die head, affecting the uniformity of the film; and then hot pressing and laminating with the coated base cloth, the number of cooling rollers is increased to three groups, the cooling roller temperature is 40°C-30°C-20°C, and the composite material is cooled and shaped step by step.

[0016] Depending on the substrate, the thickness of the laminated TPU is generally 50-400g / m 2 The proportion of polyisocyanate varies and is adjusted according to the application scenario and technical requirements.

[0017] The above-mentioned high heat load, low permeability flexible fiber-based composite fabric is applied to high-altitude balloons Compared with the prior art, the high heat load, low permeability flexible fiber-based composite fabric and preparation method described in the present invention have the following advantages: 1. This application adopts a low-temperature granulation process to develop a polyisocyanate powder material with PE as a carrier, and uses white oil to bond the polyisocyanate powder and TPU elastomer, solving the problems of uneven dispersion and uneven chemical reaction.

[0018] 2. This application introduces isocyanate cross-linking and curing process into TPU thermoplastic elastomer, and explores a complete set of melt plasticization process, opens up the extrusion casting process of semi-cured TPU elastomer, and achieves a great improvement in the thermal stability and barrier properties of TPU composite materials.

[0019] 3. The present invention provides a full-process production process for high heat load and low permeability composite materials. The composite materials have excellent performance and can be applied to various special fields such as high-altitude balloons, thus expanding the application scope of conventional TPU composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] In the attached picture: Figure 1 It is a schematic structural diagram of the flexible fiber-based composite fabric according to an embodiment of the present invention. DETAILED DESCRIPTION

[0022] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0023] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.

[0024] Embodiment 1: Step 1: Pre-treat fabric Made of 70D high-strength nylon, heat-pressed at 100°C and 80T; Step 2: Apply the adhesive layer 100 parts of two-component polyurethane, 30 parts of toluene, 2 parts of diisocyanate, 8 parts of polyisocyanate and 1 part of penetrant are mixed to form a coating; Scrape the adhesive layer, dry at 140°C, and apply 30g / m 2 , drying time 6 minutes; Step 3: Repeat step 2 and apply the coating on the other side of the base fabric; Step 4: Cast TPU The low-temperature granulation process is used to prepare polyisocyanate powder with PE as the carrier; the polyester TPU is pre-baked at 80 degrees Celsius to remove moisture, and the polyisocyanate powder with PE as the carrier, thermoplastic polyurethane elastomer, and white oil are 2 parts, 100 parts, and 3 parts respectively. Under the dew point dry state of -40 degrees Celsius, the materials are automatically mixed by the metering scale and enter the screw. The temperature of the screw extrusion section is 140°C, the temperature of the connecting section is 160°C, the temperature of the die head is 190°C, the extrusion speed is controlled at 8rmp, the extruded melt is hot-pressed and laminated with the coating base fabric, the temperature of the laminating roller is 60°C, and the lamination thickness is 50g / m 2 .

[0025] Step 5: Repeat step 4 to fit the other side.

[0026] Table 1: Test data of Example 1 and 70D high-strength nylon traditional coating process materials project Test Standards 70D high-strength nylon traditional coating process material Example 1 Weight g / m2 GB / T4669-2008 153 150 Breaking strength (N / 5cm) GB / T3923.1-2013 629 650 Tearing strength (N) GB / T3917.2-2009 7 7 Helium permeability L / ㎡.d.atm GB / T 1038-2000 1.4 0.8 Seam strength (N / 2*5cm) GB / T3923.1-2013 603 623 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 329 512 Embodiment 2 Step 1: Pre-treat fabric Made of 2000D high-strength polyester, heat-pressed at 180°C and 100T; Step 2: Adhesive 100 parts of two-component polyurethane, 30 parts of toluene, 3 parts of diisocyanate, 8 parts of polyisocyanate, and 5 parts of penetrant are mixed to form an adhesive coating; Scrape coating adhesive layer, drying temperature 140 degrees Celsius, glue application amount 60g / m 2 , drying time 9 minutes; Step 3: Repeat step 2 to coat the other side of the base fabric; Step 4: Cast TPU The low-temperature granulation process was used to prepare polyisocyanate powder with PE as the carrier; the polyester TPU was pre-baked at 80 degrees Celsius to remove moisture, and the polyisocyanate powder with PE as the carrier, thermoplastic polyurethane elastomer, and white oil were 5 parts, 100 parts, and 3 parts, respectively. Under the dew point dry state of -40 degrees Celsius, the materials were automatically mixed by the metering scale and entered the screw. The temperature of the screw extrusion section was 150°C, the temperature of the connection section was 165°C, the temperature of the die head was 200°C, the extrusion speed was controlled at 10rmp, and the extruded melt was hot-pressed with the coating base fabric, and the lamination thickness was 300g / m 2 .

[0027] Step 5: Repeat step 4 to fit the other side.

[0028] Table 2: Test data of Example 2 and 2000D high-strength polyester traditional coating process materials project Test Standards 2000D high-strength polyester traditional coating process material Example 2 <![CDATA[Grammage g / m 2 > GB / T4669-2008 758 752 Breaking strength (N / 5cm) GB / T3923.1-2013 3814 3756 Tearing strength (N) GB / T3917.2-2009 125 123 <![CDATA[Oil permeability of liquid B (g / m 2 ·24 h)]]> GJB 4219A-2013 50 26 Static load resistance GJB 4219A-2013 Seam slippage No slippage in the joints and no cracks on the surface Seam strength (N / 2*5cm) GB / T3923.1-2013 3414 3513 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 1526 2429 Comparative Example 1: The difference from Example 1 is that: no diisocyanate is added to the first adhesive layer and the second adhesive layer, and 10 parts of polyisocyanate are added at the same time; Table 3: Test data of Example 1 and Comparative Example 1 project Test Standards Example 1 Comparative Example 1 Weight g / m2 GB / T4669-2008 150 152 Breaking strength (N / 5cm) GB / T3923.1-2013 650 653 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 100 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 0.85 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 535 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 477 Comparative Example 2: The difference from Example 1 is that: no polyisocyanate is added to the first adhesive layer and the second adhesive layer, and 10 parts of diisocyanate are added at the same time; Table 4: Test data of Example 1 and Comparative Example 2 project Test Standards Example 1 Comparative Example 2 Weight g / m2 GB / T4669-2008 150 149 Breaking strength (N / 5cm) GB / T3923.1-2013 650 651 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 110 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 0.84 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 515 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 467 Comparative Example 3: The difference from Example 1 is that: no white oil is added to the first TPU layer and the second TPU layer, and the polyisocyanate powder and thermoplastic polyurethane elastomer with PE as the carrier are 5 parts and 100 parts respectively; Table 5: Test data of Example 1 and Comparative Example 3 project Test Standards Example 1 Comparative Example 3 Weight g / m2 GB / T4669-2008 150 150 Breaking strength (N / 5cm) GB / T3923.1-2013 650 655 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 180 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 1.1 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 596 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 447 Comparative Example 4: The difference from Example 1 is that the polyisocyanate powder with PE as carrier, the thermoplastic polyurethane elastomer, and the white oil are 4 parts, 100 parts, and 1 part respectively; Table 6: Test data of Example 1 and Comparative Example 4 project Test Standards Example 1 Comparative Example 3 Weight g / m2 GB / T4669-2008 150 150 Breaking strength (N / 5cm) GB / T3923.1-2013 650 655 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 194 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 0.9 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 615 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 496 Comparative Example 5 The difference from Example 1 is that no polyisocyanate powder with PE as a carrier is added, and the thermoplastic polyurethane elastomer and white oil are 100 parts and 5 parts respectively.

[0029] Table 7: Test data of Example 1 and Comparative Example 5 project Test Standards Example 1 Comparative Example 5 Weight g / m2 GB / T4669-2008 150 151 Breaking strength (N / 5cm) GB / T3923.1-2013 650 653 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 170 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 1.4 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 599 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 337 Comparative Example 6 The difference from Example 1 is that no polyisocyanate powder with PE as carrier is added, and the thermoplastic polyurethane elastomer and white oil are 0.5 parts, 100 parts and 4.5 parts respectively.

[0030] Table 8: Test data of Example 1 and Comparative Example 6 project Test Standards Example 1 Comparative Example 6 Weight g / m2 GB / T4669-2008 150 151 Breaking strength (N / 5cm) GB / T3923.1-2013 650 653 Tearing strength (N) GB / T3917.2-2009 7 7 Peel strength (N / 5cm) HG / T 3052-2008 200 173 Helium permeability L / ㎡.d.atm GB / T 1038-2000 0.8 1.3 Seam strength (N / 2*5cm) GB / T3923.1-2013 623 599 Joint thermal load strength (N / 2*5cm) 90℃ insulation for 12h GB / T3923.1-2013 512 407 The above description is only for the preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high heat load, low permeability flexible fiber-based composite fabric, characterized in that: The invention comprises a first TPU layer, a first adhesive layer, a base fabric layer, a second adhesive layer and a second TPU layer which are arranged in sequence.

2. A high heat load, low permeability flexible fiber-based composite fabric according to claim 1, characterized in that: The first adhesive layer and the second adhesive layer include one or more of a polyurethane resin, a solvent, a diisocyanate, a polyisocyanate, and a polyether siloxane copolymer.

3. The high heat load, low permeability flexible fiber-based composite fabric according to claim 1, characterized in that: The first adhesive layer and the second adhesive layer both include, by mass fraction: 100 parts of polyurethane resin, 20-30 parts of solvent, 2-3 parts of isocyanate, 8-10 parts of polyisocyanate, and 1-5 parts of polyether siloxane copolymer.

4. The high heat load, low permeability flexible fiber-based composite fabric according to claim 1, characterized in that: The first TPU layer and the second TPU layer include thermoplastic polyurethane elastomer, polyisocyanate powder with PE as carrier, and white oil.

5. The high heat load, low permeability flexible fiber-based composite fabric according to claim 1, characterized in that: The first TPU layer and the second TPU layer include 100 parts of thermoplastic polyurethane elastomer, 1-10 parts of polyisocyanate powder with PE as carrier, and 2-4 parts of white oil by mass fraction.

6. The high heat load, low permeability flexible fiber-based composite fabric according to claim 1, characterized in that: The base fabric layer is one of high-strength nylon or high-strength polyester.

7. A method for preparing a high heat load, low permeability flexible fiber-based composite fabric according to any one of claims 1 to 6, characterized in that: The steps include: S1: hot rolling treatment of both sides of the base fabric; S2: mixing the materials of the adhesive layer to obtain a coating of the adhesive layer, and coating both sides of the base fabric with a scraper to obtain a coated base fabric; S3: The PE powder containing polyisocyanate, white oil and TPU that have been granulated and crushed at low temperature are mixed into the screw in proportion, and the mixed melt is preheated to form a semi-cured cross-linked elastomer, which is then hot-pressed and laminated to the two sides of the coated base fabric obtained in step S2, and cooled and shaped in steps to obtain a flexible fiber-based composite fabric.

8. The method for preparing a high heat load, low permeability flexible fiber-based composite fabric according to claim 7, characterized in that: The hot rolling temperature in step S1 is 160-180°C, and the hot rolling pressure is 80-100T; Step S2 comprises coating both sides of the base fabric to obtain the coated base fabric, which comprises coating one side of the base fabric first, drying at 140-160°C, and applying sizing at 20-40 g / m 2 , drying time 3-6 minutes, repeat the above operation and coat the other side.

9. The method for preparing a high heat load, low permeability flexible fiber-based composite fabric according to claim 7, characterized in that: Step S3 includes mixing PE powder containing polyisocyanate, white oil, and TPU particles that have been granulated and crushed at low temperature, and automatically mixing them into a screw through a metering scale in a dew point dry state at -40 degrees Celsius. The temperature of the screw extrusion section is 140-150 degrees Celsius, and the temperature of the connection section is 155-165 degrees Celsius. The mixed melt is preheated, the die head temperature is set to 180-200 degrees Celsius, the extrusion speed is controlled at 8-10 rpm, and the cooling roller temperature is 40-30-20 degrees Celsius. The two sides of the coated base cloth obtained in step S2 are then hot-pressed and bonded, and the flexible fiber-based composite fabric is obtained by step cooling and shaping.

10. The fabric prepared according to the method for preparing a flexible fiber-based composite fabric with high heat load and low permeability according to any one of claims 1 to 6 or a flexible fiber-based composite fabric with high heat load and low permeability according to any one of claims 8 to 9 is applied to high-altitude balloons.

Citation Information

Patent Citations

  • Modified (CYCLO)aliphatic polyisocyanate mixtures, preparation thereof and use thereof

    CA2139535A1

  • Phosphorus-containing polyisocyanate and preparation method thereof

    CN102050836A

  • Environment-friendly flexible compound fabric and preparation method thereof

    CN117587642A

  • Adhesive for lamination

    JP2011102387A